Standardized Precipitation Index (SPI) For The Characterization Of Meteorological Droughts In The Town Of Guanare, Portuguesa State, Venezuela - et. al., Danny Villegas Rivas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study was to characterize the meteorological drought in the town of Guanare, Portuguesa state. The information used for the study was obtained from the meteorological data record, from the monthly precipitation series of the Aeropuerto-Guanare meteorological station of the Portuguese state for the period 1982-2015. The Standardized Precipitation Index (SPI) was used for a monthly scale of the period under study, which allowed the identification and description of the drought phenomenon, specifying its intensity, duration, magnitude and frequency of occurrence. According to the SPI values ​​obtained, it was obtained that the level of extreme drought intensity in the locality during the 1982-2015 period was very low, not exceeding 2% and being rare with extremely strong magnitudes. These meteorological drought events occurred coincidentally for the period evaluated between the months of December and March; while the months of highest humidity were between the months of May, June and July. By virtue of the results obtained, it is important to take into account the vulnerability to drought events of the social, water and agricultural sectors of the area.